1988
DOI: 10.1161/01.str.19.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Combination of aminocaproic acid and nicardipine in treatment of aneurysmal subarachnoid hemorrhage.

Abstract: Antifibrinolytic drags reduce the risk of rebleeding during the first 2 weeks after aneurysmal subarachnoid hemorrhage. However, they do not lower overall mortality, largely because of an increased incidence of cerebral ischemia. The usefulness of antifibrinolytic drugs might be increased if a method to prevent or control vasospasm in patients were to be developed. We recently completed late Phase I and Phase II studies of the calcium ion blocking drug nicardipine in 67 patients treated within 1 week of subara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 19 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…The patients' clinical grades according to the World Federation of Neurological Surgeons scale 21 were II or III (Table 1). No patient was given antiplatelet drugs, and none received calcium antagonists just prior to SAH.…”
Section: Methodsmentioning
confidence: 99%
“…The patients' clinical grades according to the World Federation of Neurological Surgeons scale 21 were II or III (Table 1). No patient was given antiplatelet drugs, and none received calcium antagonists just prior to SAH.…”
Section: Methodsmentioning
confidence: 99%
“…8 We dichotomized clinical condition into good (WFNS I-III) and poor (WFNS IV and V). Based on CT scans, the bleeding severity was classified according to the Fisher classification.…”
Section: Clinical Materials and Methodsmentioning
confidence: 99%
“…A number of studies using both antifibrinolytics and either nicardipine or nimodipine reported decreased rebleeding, no increase in ischemic deficits, and improved outcomes [15,26,28,41,42]. Rebleeding rates ranged from 7% to 13% and mortality ranged from 11% to 12%.…”
Section: Other Non-randomized Clinical Trialsmentioning
confidence: 99%
“…Different doses as well as routes of administration had been used in earlier trials, and effective blood and CSF drug levels might not have been achieved [22][23][24][25]. In addition, studies have shown that calcium channel blocking agents can decrease the incidence of vasospasm and cerebral ischemia among patients treated with antifibrinolytics [26][27][28]. Although long-term use of antifibrinolytic agents in aSAH is no longer an accepted practice, there still might be a role for short-term administration to reduce early rebleeding.…”
Section: Introductionmentioning
confidence: 99%